Avances de la Declaratoria “Riobamba, Ciudad Latinoamericana por el Comercio Justo” y sus implicaciones en el Desarrollo Local - Caterine Gabriela, Gaibor Gaibor (2022)
ABSTRACT: The research aims to determine the progress of the declaration "Riobamba Ciudad Latinoamericana por el Comercio Justo" and its implications in the local development of the Riobamba city, a non-experimental cross-sectional research was designed, a variant that was used to characterize specific moments of the phenomena studied. The information collected was obtained through interviews with the members of the Comité Local de Comercio Justo to identify the progress of the declaration; surveys applied to the participants of the Feria Plaza Vida in order to identify the fair trade actions that are promoted as a meeting place between producers and consumers; and, to a sample of the citizens of the Riobamba canton to identify the degree of knowledge and awareness about fair trade and responsible consumption. In conclusion, the most important advance is the development of the Feria Plaza Vida, seen as a meeting place between the countryside and the city in conditions of justice and equity; where it is possible to live the principles of fair trade and that contributes to the local development of Riobamba in social, economic, political and environmental terms. It is recommended to influence the approval of the reform to ordinance 005 - 2015 as a public policy that will promote not only the popular and solidarity economy, but also fair trade, responsible consumption and participatory guarantee systems. Additionally, to promote educommunication campaigns for the promotion of fair trade and awareness towards responsible consumption. KEY WORDS: fair trade, local development, declaration, responsible consumption.